2012
DOI: 10.1002/pola.26101
|View full text |Cite
|
Sign up to set email alerts
|

Controllable glycosylation of polyphosphazene via radical thiol–yne click chemistry

Abstract: We describe a versatile approach to synthesize glycosylated polyphosphazenes with controllable density of glycosyl groups. These glycopolymers have been synthesized by the nucleophilic substitution of poly(dichlorophosphazene) with propargylamine and subsequent “thiol–yne” click reaction between poly[di(propargylamine)phosphazene] and 2,3,4,6‐tetra‐O‐acetyl‐1‐thio‐β‐D‐glucopyranose (SH‐GlcAc4). The polymers were characterized with FTIR and 1H NMR. We found that the high steric hindrance of SH‐GlcAc4 plays a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…mechanism in Figure 2 ). To further probe the selectivity of this reaction, the thiol-to-alkyne ratio was increased to 5:1 and under both thermal and photochemical conditions (2 h reaction times), the major product was again the mono-addition product, i.e., vinyl sulfi des (entries [8][9][10][11][12][13]. Only under very forcing conditions, extended reaction time (20 h) and a large excess of thiol (10 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…mechanism in Figure 2 ). To further probe the selectivity of this reaction, the thiol-to-alkyne ratio was increased to 5:1 and under both thermal and photochemical conditions (2 h reaction times), the major product was again the mono-addition product, i.e., vinyl sulfi des (entries [8][9][10][11][12][13]. Only under very forcing conditions, extended reaction time (20 h) and a large excess of thiol (10 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we reported that steric effects played an important role during the photochemical reaction of polymers with high local densities of alkyne groups and thiols 19. This conclusion also applies to PBAAP.…”
Section: Resultsmentioning
confidence: 69%
“…Although the thiol–yne reaction allows for the addition of two thiol molecules to an alkyne, significant steric effects can preclude some alkynes from reacting with two thiol molecules 19,22. Alternatively, the thiol–ene coupling reaction is another type of thiol‐based radical addition reaction 23.…”
Section: Introductionmentioning
confidence: 99%
“…need to go through protection/deprotection procedures for their nucleophilic substitution on PDCP. Fortunately, an extensive library of PPZs has been developed, including derivatives substituted with alkene, alkyne, or vinyl groups, for example, allylamine, 2‐aminoethyl methacrylate, allyl glycinate, methacrylic acid, and propargylamine derivatives. These PPZs with alkene and alkyne side chains can be used as secondary precursors for free‐radical polymerization .…”
Section: Part I Background and Fundamental Properties Of Ppzmentioning
confidence: 99%